Behavioral cardiovascular risk factors in HIV-infected people in France: diversity of profiles across groups requires an urgent and tailored preventive approach - (:unkn) unknown (My University, 2018)
Background. Among people living with HIV, cardiovascular risk could be markedly reduced through lifestyle improvement. However, to date behavioral cardiovascular risk factors (other than tobacco smoking) have been poorly investigated among them. Additionally, although co-occurrence of risk factors might amplify the deleterious effects of each risk factor, little is known about such risk factors clustering in this population. We aimed to examine levels, determinants and clustering of the major behavioral cardiovascular risk factors in the French HIV-infected population, in order to better target individuals with high risk profiles. Methods. The ANRS-Vespa2 survey was conducted among a national representative sample of HIV-infected people followed at hospital in France in 2011. Frequency and co-occurrence of tobacco smoking, alcohol intake, low physical activity and obesity were assessed in the HIV-infected population, overall and in each of the distinctive socio-epidemiological group composing it (men who have sex with men, intravenous drug users, sub-Saharan African migrants, non-African heterosexuals). Individual characteristics associated with each of these indicators were investigated using multivariable Poisson regression models.Results. The 2,537 participants (median time since HIV-diagnosis: 12 years) included 39.4% men who have sex with men, 11.0% intravenous drug users, 23.5% sub-Saharan African migrants and 26.1% non-African heterosexuals. Overall, 29.4% were regular smokers, 13.8% were heavy drinkers, 14.8% lacked physical activity and 8.6% were obese. Half of the participants reported at least one risk factor with co-occurrence observed in 13.8% of the sample. However, those figures varied markedly across the groups. Main risk factors profiles were 1) regular smoking, heavy drinking, low physical activity alone or combined among intravenous drug users and men who have sex with men, 2) obesity and low physical activity usually alone among sub
Keywords: African Research